Debating civilisations: Interrogating civilisational analysis in a global age - C. A. Smith, Jeremy (Manchester University Press, 2017)
Debating civilisations offers an up-to-date evaluation of the re-emerging field of civilisational analysis, tracing its main currents and comparing it to rival paradigms such as Marxism, globalisation theory and postcolonial sociology. The book suggests that civilisational analysis offers an alternative approach to understanding globalisation, one that focuses on the dense engagement of societies, cultures, empires and civilisations in human history. Building on Castoriadis's theory of social imaginaries, it argues that civilisations are best understood as the products of routine contacts and connections carried out by anonymous actors over the course of long periods of time. It illustrates this argument through case studies of modern Japan, the Pacific and post-Conquest Latin America (including the revival of indigenous civilisations), exploring discourses of civilisation outside the West within the context of growing Western imperial power.